Georgia : Technical Assistance Report on the Financial Accounts and Financial Soundness Indicators Mission. (IMF Staff Country Reports; Country Report ;, 2018)
This Technical Assistance Report discusses the findings and recommendations made by the IMF mission regarding the financial accounts (FA) and financial soundness indicators in Georgia. One main objective of the mission was to assist the National Bank of Georgia (NBG) in the compilation of quarterly flow FA by institutional sector; estimating transactions, revaluations, and other changes in the volume of assets (OCVA). It was observed that FA are being produced by the Monetary and Statistics Division for internal use only, because for public dissemination the NBG wants first to develop automatic procedures for the estimation of revaluations and OCVA in its database. It is expected that by May 2018 business intelligence software will be fully operational for this purpose.